IDENTIFICATION OF KEY GENES AND MOLECULAR PATHWAYS ASSOCIATED WITH OSTEOGENIC DIFFERENTIATION OF DENTAL PULP STEM CELLS - Wasis Syahwanda; Elsa Fitri (Journal of Stem Cell Research and Tissue Engineering, 2026)
Dental pulp stem cells (DPSCs) have emerged as promising candidates for regenerative dentistry due to their self-renewal capacity and multilineage differentiation potential, particularly in osteogenic differentiation. Understanding the molecular mechanisms underlying this process is essential for developing effective regenerative therapies. This study aimed to identify key genes and molecular pathways involved in the osteogenic differentiation of DPSCs using a bioinformatics-based in silico approach. Gene expression data were obtained from the Gene Expression Omnibus (GEO) database, specifically the GSE80614 dataset, which compared undifferentiated and osteogenically induced human DPSCs. Differentially expressed genes (DEGs) were identified using GEO2R with the criteria of p-value < 0.05 and |log fold change| ≥ 1. Functional enrichment analysis was conducted using DAVID, while protein–protein interaction (PPI) networks were analyzed using STRING and Cytoscape. The analysis revealed distinct transcriptional differences between undifferentiated and osteogenically differentiated DPSCs. Functional enrichment demonstrated significant involvement of biological processes related to extracellular matrix organization, ossification, and regulation of cell differentiation. Key signaling pathways identified included PI3K-Akt signaling, TGF-β signaling, ECM–receptor interaction, and focal adhesion pathways, all of which are closely associated with osteogenesis. PPI network analysis identified several hub genes, including RUNX2, ALPL, BMP2, and COL1A1, suggesting their central regulatory roles in osteogenic differentiation. Overall, this study provides a systematic overview of the molecular mechanisms associated with DPSC osteogenesis and highlights potential therapeutic targets for regenerative dental applications. Further experimental validation is required to confirm these findings.